The Interplay of Policy, Institutions, and Culture in the Time of COVID-19 - Fang, Sheng (World Bank, Washington, DC, 2020)
This paper examines cross-country evidence of how the Covid-19 pandemic spread and the mortality rates associated with preexisting vulnerabilities, the government’s mobility restriction policy, institutions (democracy), and culture (individualistic culture and trust). Preexisting vulnerabilities (that is, the share of the elderly, urbanization, obesity prevalence, and air pollution) increase the spread of the pandemic and/or the mortality rate. On average, the government policy delay in mobility restriction, democracy, and culture indicators are not significantly associated with the pandemic outcomes. However, government delay in restricting mobility drastically amplifies the positive association between preexisting vulnerabilities and pandemic mortality. Individualistic culture and general trust amplify the positive links between pandemic mortality and the share of elderly people or urbanization. The analysis shows that in modeling the pandemic outcomes, it is important to consider cross-country spatial interactions.